The Implementation of Strengthening Character Education in Junior High School During the Covid 19 Pandemic - Fetrimen Fetrimen (STAI Hubbulwathan Duri, 2022)
This research aimed to determine the implementation of strengthening character education based on classroom action, school culture and community participation during the COVID-19 pandemic. This was qualitatively and quantitatively research (mixed method design) by using a descriptive approach. The data were collected through interviews structured and unstructured. The interviewees of this study were stakeholders from three Junior High chools in Jakarta such principal and vice principal for curriculum. Quantitative data collected by make closed questionnaires consisting of statements that have the answer 'yes' or 'no' and giving reasons for the choices given by respondents in choosing answers according to their choices. Questionnaires were given to 20 educators as respondent. Data analysis used constant comparative method by Glaser and Strauss. The findings of this study showed that schools still implemented of strengthening character education based on classroom action, school culture and community participation during the COVID-19 pandemic. This research has implication for understood by students about of main values strengthening character education during online learning process from home.